On the formal/substantive opposition: four interdisciplinary approaches on the same subject - Roales Buján, Oliver (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The modern scientificist thought that seeks to obtain certainty through the search for indisputable statements about irrefutable facts derived from the protocolization and standardization of procedures that take us away from the debate on particular values and interests, has forgotten that the formalization required for the design of any procedure applicable to specific cases always involves the addition of purposes related to values and interests. This oversight, typical of modern thought, has been accompanied by another attitude: the hyperspecialization of the disciplines, so that its consequences and the debates about them in a kind of constant reinvention of the wheel have been reproduced sterilely. Through an interdisciplinary study that highlights the common lines in paradigmatic debates in the fields of law, rhetoric, linguistics, cognitive science and symbolic artificial intelligence, as well as political theory, we intend to emphasize the inability of processual theories to satisfy an aspiration of absolute neutrality typical of postmetaphysical societies in the Habermasian sense.
Keywords: Due process; substantive due process; symbolic artificial intelligence; political philosophy; J. Rawls; J. Habermas; C. Mouffe